Impact of the coconut mite (Aceria guerreronis Keifer) on the coconut industry in Sri Lanka - I. R. Wickramananda; T. S. G. Peiris; M. T. Neil Fernando; L. C. P. Fernando; S. Edgington (International Coconut Community, 2007)
The coconut mite (Aceria guerreronis Keifer) was first reported in Sri Lanka in 1997. Since then it has been a serious threat to the coconut industry. Feeding of coconut mites beneath the perianth of developing nuts result in scarring of the nut surface. In severe infestations, reduced nut size and nut malformation can also occur. A survey was carried out during 2003/2004 in five mite infested zones (MIZ) of Sri Lanka to assess the impact of coconut mite on various sectors of the coconut industry. The percentage of damaged nuts due to coconut mite was significantly different between the MIZ. There were also variations relative to nut size and shape. Irrespective of spatial and temporal variability, nut loss per mite infested palm was estimated to be 15.9% per annum. A 2-3% slowing down in the growth of annual national coconut production was projected due to coconut mite infestation. The loss to the coconut grower, selling at the rate of SLR 15/nut, was estimated to be Sri Lankan Rupee (SLR) 6240/ha (57.25 US/ha) if the estate was mite infested. The de-husked weight and fresh husk weight of a coconut nut were also significantly different in relation to the mite damage and nut size and shape. From a randomly selected 10,000 nuts, the reduction of fresh husk weight was approximately 15% as a result of mite infestation, together with a loss of around 195 kg of desiccated coconut. All of the impact indicators varied significantly both spatially and temporally.